The Important Role of New Media During the COVID-19 Pandemic - Lestari, Martha Tri; Purnama, Hadi; Diniati, Anisa (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2022)
March 2020 became the beginning of a global phenomenon for global citizens when the World Health Organization (WHO) designated it as an “extraordinary event” that became known as the COVID-19 pandemic. More media, especially social media, are reporting on issues related to the pandemic. This research aims to analyze the important role of new media as a new tool that is applied during the current pandemic, using qualitative descriptive methods. The research results show that in this pandemic era, the use of new media has become a new “habit”. Every day, community activities, starting from work and schooling, have used new media, such as online channels that can support work or school activities as if done face-to-face. Currently, there are a number of activities carried out by the community using new media such as the Zoom Meeting application, Google Meet, IG Live, Youtube, WhatsApp Video, IG Video, and even other applications that may be custom-made by several company agencies to support the continued running of activities, in times of this pandemic. So, it can be concluded that current activities by the community during a pandemic era such as Work from Home (WFH) or School from Home (SFH), has become a pattern of cultural change in the society during a pandemic.